Optimizing the use of interpolated tests: The influence of interpolated test lag - Lavigne, Eric; Risko, Evan F. (APA PsycNet, 2018)
The use of recorded lectures is increasing rapidly provided growth in online learning. One technique that can be used to improve learning from recorded lectures is interpolated testing – the presentation of tests throughout the recorded lecture. In the present investigation, we examine a critical question with respect to the implementation of interpolated testing in recorded lectures. Where should the tests be located relative to the tested material? Specifically, we examine the influence of the lag between the presentation of the to-be-remembered material and the interpolated test. Across two experiments we compare an immediate test condition (i.e., a test immediately after the relevant information is presented) and a delayed test condition (i.e., a test is presented about 3 minutes after the relevant information is presented). When no feedback was provided immediate interpolated testing was superior to delayed interpolated testing. There was no difference when feedback was provided. Implications of the present results for implementing interpolated testing in educational contexts are discussed.
This version of the article may not completely replicate the final authoritative version published: https://psycnet.apa.org/fulltext/2018-65290-002.html. It is not the version of record and is therefore not suitable for citation.
Keywords: testing; lectures; memory